Extracorporeal photopheresis therapy rapidly changes the cytokine profile and tumor microenvironment in cutaneous T cell lymphoma - Melchers, Susanne; Tengler, Luisa; Şener, Özge Ç.; Beltzig, Paul L.; Schmidt, Ronny; Klein, Stefan; Utikal, Jochen S.; Nicolay, Jan P. (Frontiers in Immunology, 2025)
Primary cutaneous T cell lymphomas (CTCL) are a heterogeneous group of rare lymphoproliferative disorders originating in the skin. Extracorporeal photopheresis (ECP) is an established, effective and excellently tolerable CTCL therapy, that can also be applied for the treatment of graft vs. host disease (GvHD). However, the underlying molecular mechanisms of ECP have not yet been fully clarified and seem to be dependent on the underlying disease. In this study, peripheral blood samples collected from six CTCL and three GvHD patients were analyzed pre- and post-ECP within one treatment of ECP for short-term alterations in the cytokine and chemokine milieu in the plasma and the composition of the peripheral blood mononuclear cell (PBMC) subsets. In CTCL, the plasma profiling revealed a lower expression of IL-15, IL-17, ICOS and higher expression of IL-13 post-ECP compared to the pre-ECP samples. Additionally, ECP led to an increased expression of the cell death inducers Fas and TRAIL. Flow cytometry revealed a significant increase in the CD14+ monocytes post-ECP in the CTCL patients, and a tendency of higher CD3+CD4- cytotoxic T cells in GvHD patient. Therefore, one cycle of ECP can induce detectable alterations in the peripheral blood of both CTCL and GvHD patients. This study contributes to the elucidation of the molecular mechanisms of ECP therapy and the detection of potential biomarkers for therapeutic response to ECP.